Chancen und Risiken eines nationalen Seehafenkonzepts. Versuch einer ökonomischen Bewertung. - Stuchtey, Rolf (DVV Media Group, 2008)
In der Zeit der rot-grünen Bundesregierung ist auf Initiative des Bundesumweltministeriums die politische Notwendigkeit eines "Nationalen Seehafenkonzepts" geprüft worden. Der Vorschlag stand in einem engen Zusammenhang mit der Forderung der Länder Bremen und Hamburg, die Weser und Elbe an die Werfttiefgänge der zu der Zeit geplanten oder im Bau befindlichen Großcontainerschiffe anzupassen. Das im Wesentlichen zuständige Bundesverkehrsministerium hat diese Forderung in der Form nicht übernommen. Stattdessen sollte ein vom Umweltministerium vergebenes, aber von Experten des Verkehrsministeriums begleitetes Gutachten zunächst Entscheidungshilfen erarbeiten.

The varying responsibilities held, on the one hand, by coastal Länder for infrastructure facilities at seaports and, on the other hand, by the federal government for the in-dispensable link-up with the hinterland and onward transport by inland shipping have, repeatedly, led to demands for a national seaport concept. Discussions are again underway at a time when certain infrastructure shortcomings in general, and at seaports in particular, have become rather obvious. The limited financial resources at hand require a well-coordinated investment policy and an increase in users' contribution to cover the costs involved. Against the background of well-established and notably expanding maritime markets, the question arises about more appropriate methods of finance, prompted by overstretched budgets and the time-consuming decision-making process of the concerned coastal Länder. A review of the responsibilities held by the federal government and the Länder would be appropriate. There is a marked gap between the costs and benefits concerning seaport infrastructure investment. Whereas the coastal Länder shoulder such costs in full, the benefits are shared by all federal states as well as by EU neighbours. The Federal Commission will have to deal with all these aspects since, apart from the range of responsibilities, the financial balance on a vertical and horizontal level appears to be affected.
Chances and risks associated with a national seaport concept - an attempt of an economic appraisal.
Keywords: Verkehr; Wasserverkehr; Seehafen; Verkehrsinfrastruktur; Entscheidungshilfe; Verkehrspolitik; Verkehrsplanung; Wettbewerb; Hafenplanung; Hafenwirtschaft